The Effect Of Hypertension Exercise On Lowering Blood Pressure In The Elderly In The Work Area Of The Gunung Kaler Health Center In 2023 - Patimah Patimah; Achmad Fauzi (CV. Inara, 2024)
Background Elderly people often experience high blood pressure due to natural aging causing decreased elasticity of blood vessels which can increase blood pressure. Purpose ofWriting: to find out the Effect of Hypertension Exercise on Lowering Blood Pressure in the Elderly in the Work Area of the Gunung Kaler Health Center in 2023. Research Methods: The method in this study was a Quasy Experiment with a one group pretest-posttest design. The population in this study were all elderly people who experienced hypertension. The data collected was primary data using observation. The dependent variable was a decrease in blood pressure. The independent variable was postpartum exercise. Data processing. SPSS. The results of the study showed that the assessment before and after the intervention group obtained a Sig value of 0.000, a sig value <0.05 which can be concluded that there is an effect of hypertension exercise on reducing blood pressure. Meanwhile, the before and after assessment in the control group obtained a Sig value of 0.215, a sig value > 0.05 which can be concluded that there was no effect of hypertension exercise on reducing blood pressure.Conclusions and Suggestions: Health workers can provide information about the need for education and practice to be carried out by health workers together with the elderly to implement hypertension exercises carried out in predetermined homes, it should be done routinely according to predetermined rules for doing hypertension exercises.